IDENTIFICATION OF VULNERABILITY AREA OF MASS MOVEMENT USINGSTORIE METHOD IN BONE BOLANGO REGENCY, GORONTALO PROVINCE - Joni Djakun; Sri Maryati; Muh. Kasim (Geographica: Science and Education Journal, 2020)
Based on the analysis result, the research sites are divided into three levels of mass movement vulnerability; low as much as 10,98, moderate as much as 84,41, and high as much as 4,61% out of the entire research areasMass movement occurs due to the natural process in the changes of surface structure, in which there is a disturbance of stability in the soil or rocks making up the slope. The disturbance is caused by some conditions such as a relatively steep slope, the condition of rock or soil making the slope, high rainfall intensity, uncontrolled human activity in exploiting the nature as well as the state of geological structures. The research site is located in three sub-districts in Bone Bolango District; Suwawa Timur, Suwawa Tengah, and Suwawa Selatan. These three sub-districts have a history of mass movement during the rainy season. The availability of up-to-date data is required to reduce the impact caused by the mass movement. This research aims to identify the areas prone to mass movement. One of the approaches applied to identify the areas prone to mass movement is Storie Index method by calculating the parameter, which is considered influencing the mass movement. Among others, the parameters are steepness of the slope, rainfall, type of soil, land usability, and lineament density as the parameter of geological structures.